Upaya Guru dalam Mengatasi Kesulitan Belajar Peserta Didik pada Mata Pelajaran PAI di SDN 1 Rupe Kabupaten Bima - Ratri Evianti; A. Marjuni; Rosdiana (Primer Edukasi Journal, 2023)
This study aims to determine the supporting factors and inhibiting factors of students in PAI subjects at SDN 1 Rupe Bima Regency, and to determine the efforts of PAI teachers in overcoming student learning difficulties in PAI subjects at SDN 1 Rupe, Bima Regency. This research used a qualitative research method with the subject of research by the Principal and PAI Teacher at SDN 1 Rupe. The data sources used in this study are primary data sources, namely teachers and students and secondary data sources, namely references or relevant books. The research approach used in this study is a phenomenological approach. The techniques of data analysis and processing used in this study are descriptive qualitative. The results of this study were obtained as follows: (1) Supporting factors found the availability of adequate facilities, namely the provision of musholah, books and the Qur'an in supporting teaching and learning activities, the availability of this facility makes it easier for teachers to make efforts to overcome student learning difficulties at SDN 1 Rupe. (2) The inhibiting factor was found that there was a lack of time in the PAI learning process, because the time given was only 1 meeting every week, so parental support was needed, especially in teaching to read the Qur'an. 3) Teachers strive to teach students, teachers strive to foster students to be able to master the learning given, teachers increase learning time, namely holding tutoring and imtek guidance, and are supported by giving gifts that can increase the motivation of students to be more serious in receiving material, teachers are able to provide good examples or instructions to their students. In overcoming the difficulties of learning to read the Qur'an, teachers specifically teach their students during extracurricular activities.